Vivekananda: Indian Swami and Global Guru - Harris, Ruth (Religions, 2023)
This article seeks to integrate the “Indian swami” with the “global guru” and reflects upon why Vivekananda’s teaching was conveyed so differently to different audiences. It argues that Vivekananda’s distinctive form of “counter-preaching” had its roots in Adhikari-bheda, a tradition that seeks to tailor spiritual instruction to the needs and capacities of individual aspirants. I will show how he applied this technique to larger audiences because he believed that “truth” had a relative dimension that had to account for cultural difference. I investigate how instruction in Hindu “man-making” and spiritual democracy in India was matched by lessons designed to counter “muscular Christianity” in Euro-America. Vivekananda wanted both to reinforce a vision of eastern wisdom and counter western (and at times Indian) prejudices, whilst also attempting to shift entrenched but fallacious generalizations in each arena. In working within this seeming contradiction, I will show how his nationalism and universalism were inextricable, and also tied to his innovative formulations of Advaita Vedanta, karma yoga, and especially “practical Vedanta”. I will conclude by explaining how his methods generally sought to pull his audiences away from extremes. The kaleidoscopic qualities of his teachings, I will suggest, explain why his legacy has been so variously deployed by both the right and left in contemporary Indian political culture.